CFD Analysis on the Aerodynamic Characteristic of Medium Sized-Car Vehicle Moving Under the Influence of Steady Crosswind - Muhammad Hamizan Noor; Izuan Amin Ishak (Journal of Automotive Powertrain and Transportation Technology, 2024)
Vehicle aerodynamics is a critical issue to investigate, particularly for those concerned with safety criteria. For instance, the issue of crosswind effect on a moving car vehicle is an example of a critical road safety driving situation. In this article, Computational Fluid Dynamics (CFD) analysis is carried out using ANSYS Fluent software to investigate the influence of crosswind on a moving car vehicle. The car model used in this study will be a medium-sized vehicle from the C-segment (i.e the sedan car). The manipulating variables in this study will be the yaw angle (i.e the different crosswind conditions) which are 0°, 15°, 30°, 45°, 60°, 75° and 90° and different of inlet velocity 10m/s and 30 m/s. The analysis of the aerodynamic loads (i.e side force, lift force and drag force) and associated flow structures is carried out to measure the aerodynamic behaviors when the car is moving under different crosswind conditions. From the result obtained, it shows that the different yaw angles affect the aerodynamic performance and the stability of the vehicle itself. However, the effect of different vehicle speeds is not many changes in terms of aerodynamic loads. When the yaw angle increased, the side force is also increased and the stability of the car is decreased. Conclusively, the highest side force occurs when the yaw angle is at 90°. In terms of the flow structures, because of the flow separation, the high-pressure region gradually migrated more to the windward area and the low-pressure region shifted to the leeward area and the top of the vehicles as the yaw angle grew.